Post-operative Pancreatitis as a Predictor of Postoperative Pancreatic Fistula in Patients Following Pancreaticoduodenectomy - Subedi, Nirajan; Ghimire, Bikal; Kansakar, Prasan B S; Bhandari, Ramesh S; Lakhey, Paleswan J; Singh, Yogendra P (Journal of Nepal Health Research Council, 2023)
Background: Postoperative pancreatic fistula remains the single most important determinant of morbidity and mortality following pancreaticoduodenectomy. A new entity was proposed by Saxon Connor “Post-Operative pancreatitis”, which is defined by raised serum amylase more than the upper limit of institutional serum amylase value on Post-Operative day 0 or 1. There has been shown to be an association between postoperative pancreatitis and postoperative pancreatic fistula. We have conducted this study to see the incidence of postoperative pancreatitis and its association with postoperative pancreatic fistula.Methods: This was a prospective observational study. All patients undergoing pancreaticoduodenectomy at a tertiary care center for one and a half years were included. A cut-off value of serum amylase 80U/L was used to make a diagnosis of postoperative pancreatitis. The patients were followed up for one month. Pancreas specific complications were defined according to the definition given by the International Study Group of Pancreatic Surgery. Results: A total of 49 pancreaticoduodenectomies were done in the given period. The incidence of postoperative pancreatitis was 31(63.3%) and postoperative pancreatic fistula was 19(38.8%). Postoperative pancreatic fistula was seen in 19(61.2%) of patients having postoperative pancreatitis (P<0.001). Post-operative pancreatitis was also significantly associated with post pancreatectomy hemorrhage, increased hospital stay, and mortality. In multivariate analysis, preoperative endoscopic biliary drainage and increased serum amylase on the first postoperative day came out to be an independent predictor of postoperative pancreatic fistula.Conclusions: Post-operative Pancreatitis was associated with an increased incidence of Post-operative pancreatic fistula and other postoperative complications like Post pancreatectomy hemorrhage and mortality. Keywords: Pancreaticoduodenectomy; postoperative pancreatitis; postoperative pancreatic fistula; post pancreatectomy haemorrhage